Application of multi-criteria method EDAS in tourism industry candidates' ranking and the introduction of corrective step - Štilić Anđelka; Nicić Miloš; Zimonjić Borko; Njeguš Angelina (Turističko Poslovanje, 2019)
The aim of this paper is to present a relatively new method of multi-criteria analysis -EDAS and to demonstrate its applicability in tourism industry candidates' ranking. An example of the use of the EDAS method outlined here is authentic; wider segment of the survey and use of real data and requirements led to real problems and in order to solve them, extension of EDAS was developed: EDAS+; that was tested and yielded satisfactory results.